2022
DOI: 10.3389/fnut.2022.801582
|View full text |Cite
|
Sign up to set email alerts
|

Body Roundness Index and Waist–Hip Ratio Result in Better Cardiovascular Disease Risk Stratification: Results From a Large Chinese Cross-Sectional Study

Abstract: BackgroundThe appropriate optimal anthropometric indices and their thresholds within each BMI category for predicting those at a high risk of cardiovascular disease risk factors (CVDRFs) among the Chinese are still under dispute.ObjectivesWe aimed to identify the best indicators of CVDRFs and the optimal threshold within each BMI category among the Chinese.MethodsBetween 2012 and 2020, a total of 500,090 participants were surveyed in Hunan, China. Six anthropometric indices including waist circumference (WC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 62 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…Many previous studies have indicated that WHT.5R and BRI are more strongly associated with the risk of cardiovascular disease and metabolic syndrome than BMI, WC, or WHtR [18,20,21], but it is unclear whether there is an association between WHT.5R and BRI and the risk of multimorbidity. Our results demonstrate that WHT.5R and BRI are independently and positively associated with the risk of multimorbidity, and both are more strongly associated with multimorbidity than BMI and WHtR but weaker than WC, suggesting that WHT.5R and BRI are better than BMI and WHtR in screening for multimorbidity.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have indicated that WHT.5R and BRI are more strongly associated with the risk of cardiovascular disease and metabolic syndrome than BMI, WC, or WHtR [18,20,21], but it is unclear whether there is an association between WHT.5R and BRI and the risk of multimorbidity. Our results demonstrate that WHT.5R and BRI are independently and positively associated with the risk of multimorbidity, and both are more strongly associated with multimorbidity than BMI and WHtR but weaker than WC, suggesting that WHT.5R and BRI are better than BMI and WHtR in screening for multimorbidity.…”
Section: Plos Onementioning
confidence: 99%
“…In addition, a new geometric index that combines height, waist circumference (WC), and hip circumference (HC) has been proposed and used, specifically, the body roundness index (BRI) [19]. Some studies have revealed that BRI is significantly associated with the occurrence of metabolic syndrome, insulin resistance, and CVD [20,21]. Although the above measures have been widely used in various studies, most of the previous studies were based on a cross-sectional design and tended to focus on the association between a single indicator of obesity and multimorbidity and the relationship between different obesity indicators and their dynamic changes and multimorbidity has not been systematically estimated.…”
Section: Introductionmentioning
confidence: 99%
“…The WHR reference values are gender specific. For males, physiologically WHR is >0.90 and for females >0.85 [ 74 ].…”
Section: Characteristics Of Adipose Tissuementioning
confidence: 99%
“…The pathogenesis of MetS is influenced by genetic and lifestyle factors [ 85 ]. In patients with MetS, lifestyle modifications, and in some cases, pharmacological treatment, are required for improving patient outcome [ 3 , 74 ]. A lack of effective intervention in patients with MetS may lead to developing other CMDs, such as CVD, disability, and premature death [ 84 ].…”
Section: Characteristics Of Adipose Tissuementioning
confidence: 99%
“…This index serves as a proxy for total and visceral body fat [ 29 ]. It shows good discriminatory power for metabolic syndrome in adults of both sexes from diverse populations [ 30 ] and is superior to other anthropometric measures for determining the presence of cardiovascular disease risk factors [ 31 ]. Moreover, BRI also provides a method to visually compare individual body types and identify the body type location relative to a healthy reference range: briefly, it can be applied as a visual tool for health status evaluations [ 29 ].…”
Section: Assessment Of Waist and Hip Circumferencesmentioning
confidence: 99%